A review of the cascade refrigeration system - Rachman, Arfidian; Yuana Dewi, Arfita; Effendi, Asnal (Jurnal Teknologi dan Vokasi, 2026)
This article presents a comprehensive literature review of the cascade refrigeration system (CRS), a crucial technology capable of reaching evaporation temperatures as low as -170°C while extending the operational range of conventional refrigeration systems. The discussion encompasses various CRS design configurations, refrigerant analyses, and system optimization efforts. Furthermore, the paper identifies the influence of specific parameters on system performance, economic analysis, and practical applications, concluding with recommendations for future research.